2021
DOI: 10.1186/s12915-021-01164-4
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale characterization of drug-induced microtubule filament dysfunction using super-resolution microscopy

Abstract: Background The integrity of microtubule filament networks is essential for the roles in diverse cellular functions, and disruption of its structure or dynamics has been explored as a therapeutic approach to tackle diseases such as cancer. Microtubule-interacting drugs, sometimes referred to as antimitotics, are used in cancer therapy to target and disrupt microtubules. However, due to associated side effects on healthy cells, there is a need to develop safer drug regimens that still retain clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…These latter findings align with published in vitro experiments demonstrating kinesin-1-induced MT damage (Andreu-Carbó et al, 2021;Budaitis et al, 2021;Dumont et al, 2015;Triclin et al, 2021;VanDelinder et al, 2016), MT curling observed in kinesin-1-based gliding assays in vitro (Hahn et al, 2019;Lam et al, 2016), and the curling observed upon kinesin-1 activation in non-neuronal cells (Paul et al, 2020;Randall et al, 2017). Notably, MT curling is not specifically linked to motor proteins, but is similarly observed upon loss of various MT-binding and -regulating proteins (Hahn et al, 2019) and in a model of chemotherapy-induced peripheral neuropathy (Rozario et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…These latter findings align with published in vitro experiments demonstrating kinesin-1-induced MT damage (Andreu-Carbó et al, 2021;Budaitis et al, 2021;Dumont et al, 2015;Triclin et al, 2021;VanDelinder et al, 2016), MT curling observed in kinesin-1-based gliding assays in vitro (Hahn et al, 2019;Lam et al, 2016), and the curling observed upon kinesin-1 activation in non-neuronal cells (Paul et al, 2020;Randall et al, 2017). Notably, MT curling is not specifically linked to motor proteins, but is similarly observed upon loss of various MT-binding and -regulating proteins (Hahn et al, 2019) and in a model of chemotherapy-induced peripheral neuropathy (Rozario et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The general shape of the microtubule network in the enlarged images (j,l) is consistent between live and fixed images, with the same extensive curvature observed in (j) and the two microtubules crossing each other in (l) indicating preservation of the structure through the membrane removal process. The time from finishing live-cell image acquisition to finishing fixation was approximately 20 min, which is enough time for some movement and polymerization/depolymerization of the microtubule network to occur, but not enough time for substantial rearrangement . This is revealed in the comparison between pre and post fixation, Figure d, where some features of the network can be observed in both imaging modes while being slightly displaced or distorted.…”
Section: Resultsmentioning
confidence: 99%
“…The time from finishing live-cell image acquisition to finishing fixation was approximately 20 min, which is enough time for some movement and polymerization/depolymerization of the microtubule network to occur, but not enough time for substantial rearrangement. 33 This is revealed in the comparison between pre and post fixation, Figure 2d, where some features of the network can be observed in both imaging modes while being slightly displaced or distorted. In particular, Figure 2f−m highlights two such regions, one where multiple microtubules start curving back on themselves and the other at a microtubule crossing point.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Aberrant nuclear membrane phenotypes have been associated with disease pathologies ( Muchir and Worman 2004 ; Fichtman et al, 2019 ). Examination of whole nuclei morphology with the detail from super-resolution imaging could enhanced visualization of previously uncharacterized structural changes brought about by virally-induced differentiation ( Li et al, 2021 ), genetic anomalies, or drug treatments ( Rozario et al, 2021 ). The nuclear lamina, as imaged in this work via lamin B1, also provides a distinct outline of the nucleus.…”
Section: Discussionmentioning
confidence: 99%